Implementasi Metode Pembelajaran dan Evaluasi Pembelajaran di Pondok Pesantren Lirboyo - Azka, Muahmmad Faza; Masita, Azza; Kibtiyah, Asriana (Lembaga Yasin AlSys, 2024)
The study assesses a learning and teaching process that has been done and done in the lirboyo lodge that some of the applied methods may contribute to a learning evaluation. With teaching methods characterized by boarding schools, it will bring new variations and innovations in education. Learning assessments in boarding schools are also developing according to the anthrax environment. The study taken on both the smooth and quality of the work is the approach that researchers use in the study is a qualitative descriptive approach. Because the orientation of research is based on natural phenomena or phenomena. Analysis used using the mills hubberman model (1) the data reduction (reduction of data), verification (data presentation), inequality or verification (drawing conclusions and verification). Research shows that some methods employed by ustadz in learning activities, requiring a teacher's ability and skill in applying relevant methods with purpose becoming a must be developed in a good non-forma class, as well as having a method of learning done is expected to produce a success in learning. Such success can be obtained through application of the type of evaluation tool.